If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + -1X = V Reorder the terms: -1X + Y = V Solving -1X + Y = V Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1Y' to each side of the equation. -1X + Y + -1Y = V + -1Y Combine like terms: Y + -1Y = 0 -1X + 0 = V + -1Y -1X = V + -1Y Divide each side by '-1'. X = -1V + Y Simplifying X = -1V + Y
| 42=13+x+12 | | 17.50(x+400)=315 | | N-8n= | | 12+x+7=26 | | (6x+4)2=-16 | | 4.95+1.25n=10 | | Z-17=34 | | 5r-16=r | | 8xh=8 | | 28a-a= | | 1-5x=x+15 | | 4.00x-(-20.00)=20.00 | | 8.4u-2.3=27.1 | | 2a+8a=3 | | 5(w-4)-1=-3(-8w+8)-4w | | 19+x=81 | | 4.00x-(-20.00)=200.00 | | 16x^2-4=96 | | (5*3)-(m+4)=7 | | 4.00x-(200.00)=200 | | 1.4e+2=10.4 | | 16x^2+25y^2+100y-300=0 | | 56*4= | | -3y+7(y+4)=-4 | | 5x+5y=8y+8 | | 5v+2=8(v+1) | | -6v+2(v-7)=22 | | 2r^2+2=5r | | 20=2(x-4)+2x | | 1.5t-150=450 | | 5w+9=-31 | | 2r^4+46r^2-100=0 |